Backward and simultaneous masking measured in children with language-learning impairments who received intervention with Fast ForWord or Laureate Learning Systems software. - Marler JA; Champlin CA; Gillam RB (American Journal of Speech-Language Pathology, 2001)
The developers of a computer-assisted language intervention program called Fast ForWord (FFW) have claimed that their software changes temporal processing abilities as a result of specialized modifications to the acoustic and temporal properties of the speech signal within the program. This pilot study compared changes in auditory temporal processing in children who received FFW training and in children who received training with computer-assisted language intervention programs that were not designed to improve auditory perceptual skills. Four boys with Language-Learning Impairments (LLI) and 3 boys with typical language participated. Two of the boys with LLI received the FFW program, and the other 2 received a bundle of computer-assisted instruction (CAI) programs published by Laureate Language Systems (LLS). The FFW and LLS programs were presented on the same schedule. To assess temporal processing, signal thresholds in backward and simultaneous masking conditions were evaluated just before, during, and immediately after language training. The boys with typically developing language received no training. Children with typical language produced signal thresholds in the backward masking condition that were markedly lower than those in the simultaneous masking condition. This disparity is indicative of normal temporal processing. Conversely, 3 of 4 children with LLI failed to demonstrate a simultaneous-backward difference during baseline. The lack of a difference implies that temporal processing was not normal in these children. The fourth child with LLI had signal thresholds that paralleled those of the children with normal language development. This child also had the mildest form of LLI. Of the 3 children whose temporal processing was abnormal, 2 boys showed decreased signal thresholds in the backward masking condition. However, the improvement was sudden, occurring relatively early in the training sequence, and observed with both treatment programs. The third child with abnormal temporal processing failed to show a change in backward masking at any time during treatment Over the course of the experiment, signal thresholds for all listeners decreased by similar amounts in both backward and simultaneous masking. Taken together, these results do not support the presence of a program-specific improvement in temporal processing. In addition to the temporal processing deficits revealed by backward masking, group differences in response patterns implicate auditory memory involvement or differences in maintaining attention.